Exploring the Academic Landscape: A Critical Analysis and Review of the Nepal Journal of Multidisciplinary Research [NJMR] - Mahat, Dipak; Neupane, Dasarath; Karki, Tej Bahadur (Nepal Journal of Multidisciplinary Research, 2023)
The establishment of the Nepal Journal of Multidisciplinary Research (NJMR) aimed to facilitate the exchange of knowledge among global scholars. Consequently, a thorough examination of NJMR's trajectory toward its objectives became essential. This investigation, conducted through systematic review methods, durations five years and encompasses 164 articles, including one special issue. Throughout this period, the journal exhibited growing interest across diverse areas of study, although a notable observation was the limited citations in many articles. The majority of contributions came from scholars in Nepal and India, covering a wide range of subjects. Notably, Tribhuvan University emerged as a leading contributor, particularly in the areas of software development and cultural practices, which received more citations. The predominant focus of the journal was on quantitative research; however, there is a recognized need to acknowledge and emphasize the value of qualitative findings. To enhance its academic standing, the Nepal Journal of Multidisciplinary Research [NJMR] could benefit from increased global awareness, engagement, and a more balanced approach to research methods. Gaining wider acceptance may involve fostering international collaboration and ensuring a more comprehensive representation of qualitative research within its publications. By addressing these aspects, the journal has the potential to elevate its academic impact and contribute more substantially to the global scholarly community.